2011
DOI: 10.1016/j.ab.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of six serotypes of botulinum neurotoxin using fluorogenic reporters

Abstract: a b s t r a c tMethods that do not require animal sacrifice to detect botulinum neurotoxins (BoNTs) are critical for BoNT antagonist discovery and the advancement of quantitative assays for biodefense and pharmaceutical applications. Here we describe the development and optimization of fluorogenic reporters that detect the proteolytic activity of BoNT/A, B, D, E, F, and G serotypes in real time with femtomolar to picomolar sensitivity. Notably, the reporters can detect femtomolar concentrations of BoNT/A in 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…Ruge et al recently reported the use of fluorogenic substrates, called the BoTest reporters, to develop high-throughput and sensitive assays to detect BoNT endopeptidase activity (37). For the detection of BoNT/A and BoNT/E, the BoTest A/E reporter is composed of SNAP-25 residues 141 to 206 fused to an N-terminal cyan fluorescent protein (CFP) and a C-terminal yellow fluorescent protein (YFP) (13,37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ruge et al recently reported the use of fluorogenic substrates, called the BoTest reporters, to develop high-throughput and sensitive assays to detect BoNT endopeptidase activity (37). For the detection of BoNT/A and BoNT/E, the BoTest A/E reporter is composed of SNAP-25 residues 141 to 206 fused to an N-terminal cyan fluorescent protein (CFP) and a C-terminal yellow fluorescent protein (YFP) (13,37).…”
Section: Resultsmentioning
confidence: 99%
“…Construction of the plasmid encoding the BoTest A/E reporter, pBoTest A/E, is described elsewhere (37). The BoNT/ E-specific reporter plasmid (pBoTest E) was constructed by amplifying pBoTest A/E using phosphorylated primers 5Ј-Pi-CCA ACC AAG AGG CAA CAA AGA TGC-3Ј and 5Ј-Pi-CTT CAT CAA TTC TGG TTT TGT TGG AG-3Ј (where Pi indicates phosphorylated primer), designed to introduce an R198E mutation to deactivate the BoNT/A cleavage site (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon substrate cleavage, the two fluorophores are separated, so that the fluorescence of the donor is no longer quenched and can be measured. This principle was used by different groups to detect the activity of different BoNT serotypes with sensitivities between 35 pg/mL and 150 ng/mL depending on serotype, FRET substrate, and assay time used (Anne et al 2001;Dong et al 2004;Rasooly and Do 2008;Pires-Alves et al 2009;Poras et al 2009;Gilmore et al 2011;Ruge et al 2011). The principle has also been implemented into portable devices with sensitivities in the ng/mL range (Sapsford et al 2008;Kostov et al 2009;Sun et al 2010;Balsam et al 2011) and is the basis for commercial substrates like SNAPtide Ò (Shine et al 2002).…”
Section: Endopeptidase Assaysmentioning
confidence: 99%